The private trustee in Victorian England - Stebbings, Chantal (Cambridge studies in English legal history., 2002)
The trust was a popular device among the Victorian middle classes to preserve their private property. But Victorian society was changing rapidly, which had a profound effect on the trustee. Stebbings explores the legal response to the trustee and the varied relationships experienced in the course of their administration.